Radiological status of agricultural lands of the Narodychi United Territorial Community - Yu. V. Khomutinin; M. M. Lazarev; O. V. Kosarchuk; V. V. Illienko; S. Ye. Levchuk; V. V. Pavlyuchenko; A. V. Salnikova; D. M. Lazarev; V. O. Kashparov (Ядерна фізика та енергетика)
Current radiological conditions and the possibility of returning to economic use of radionuclide-contaminated agricultural lands of the Narodychi United Territorial Community of the Korosten District of the Zhytomyr Region were assessed. The lands had been withdrawn from use in accordance with the Law of Ukraine "On the Legal Regime of the Territory Exposed to Radioactive Contamination as a Result of the Chornobyl Disaster" (Law) and marked in the State Land Cadastre of Ukraine as "radioactively contaminated land". It is shown that in accordance with the requirements of the Law on soil contamination density with 137Cs, 90Sr, 238-240Pu the lands currently do not belong to the zone of unconditional (mandatory) resettlement and even the zone of guaranteed voluntary resettlement and have no legal grounds for restrictions on their use. Predictive assessment of contamination of crops with 137Cs and 90Sr growing on the considered fields was performed. The assessments show which from the fields can be used to produce without countermeasure products below the permissible levels.